Justice and social reconstruction in the aftermath of genocide in Rwanda: an evaluation of the possible role of the gacaca tribunals - Sarkin, Jeremy (University of Pretoria, 2006)
Prepared under the supervision of Professor Jeremy Sarkin, Faculty of Law, University of the Western Cape